Post-operative Pain Outcomes of Laparoscopic Ventral Hernia Repair (LVHR): An eight-year experience - Shahid Rasul; Hassan Ahmed; Sanum Ali; Surrendar Dawani; Sarah Zahid; Sehrish Hussain; Salman Jafferi; Mansab Ali (Journal of Bahria University Medical and Dental College)
Objective: To evaluate post-operative pain, recovery time and standard of living in patients undergoing LVHR in detail. Study design and Setting: This prospective cohort study was conducted at a tertiary care hospital of Karachi, Pakistan, after getting approval from the “National Medical Centre Ethical Review Board”, from January 2011 to December 2019, Methodology: Total n= 577 patients undergoing standard LVHR procedure (defect closed with non-absorbable monofilament suture, reinforced with intra-abdominal dual layer mesh, anchored with non-absorbable tacks & sutures). Patient demographics, perioperative & postoperative findings and post-operative pain analysis were investigated and presented as descriptive statistics. Follow-up was carried out at 1st week, 2nd week, 3rd monthly, 6 monthly and 12 monthly post-operative appointments. Results: During the study period of nine years (January 2011 to December 2019), 577 patients (primary ventral hernia n=232, recurrent ventral hernia n=188 patients, incisional hernia n=157) underwent LVHR. Mean post-operative hospital stay was 1.53 ± 1.8 days. Mean post-operative pain assessment on visual analog scale (VAS) after surgery (0-3days) was reported to be 38.5±29 by 65 patients out of 577 (11.26%), which significantly decreased at the end of 1st week to 27.9 ± 25.6. Only 3 patients (0.51%) reported chronic pain during the span of 3-6 months. Conclusion: LVHR was associated with considerably less post-operative pain, shorter hospital stay and reduced time of convalescence. It is demonstrated that LVHR to be a safe and superior approach for the repair ventral hernias.